Association of changes in commute mode with body mass index and visceral adiposity: a longitudinal study - Keisuke Kuwahara; Hisashi Noma; Tohru Nakagawa; Toru Honda; Shuichiro Yamamoto; Takeshi Hayashi; Tetsuya Mizoue (BMC, 2019)
Abstract Background Prospective data are sparse for active commuting to work and body weight in Asia. We assessed the association of 5-year changes in commuting mode with body mass index (BMI) and the indicators of abdominal obesity in Japanese working adults. Methods In this longitudinal study, we studied 29,758 participants (25,808 men and 3950 women) in Japan aged 30 to 64 years at baseline who underwent further health examination 5 years after the baseline examination. Changes in BMI were calculated from objectively measured body height and weight at baseline and follow-up examination. Visceral and subcutaneous fat areas and waist circumference measured by computed tomography scans were used as indicators for abdominal adiposity. Linear regression was applied to estimate the association of changes in commuting mode with the obesity outcomes. Results Within the 5-year study period, adults who maintained inactive commuting gained weight, and compared with this group, adults who switched to inactive commuting had higher weight gain; conversely, adults who switched to active or public transportation commuting and especially those who maintained active or public transportation commuting experienced less weight gain. Subgroup analysis showed similar tendency across the different transitions of leisure-time exercise or occupational physical activity. For example, among adults who maintained no exercise (n = 16,087), the adjusted mean (95% confidence intervals) of the BMI change over 5 years in kg/m2 were 0.27 (0.24 to 0.30) for maintained inactive commuting group (reference), 0.34 (0.30 to 0.38) for switching to inactive commuting group (P = 0.046), 0.20 (0.18 to 0.22) for switching to active commuting or public transportation group (P = 0.001), and 0.09 (0.06 to 0.13) for maintained active commuting or public transportation group (P < 0.001). Maintained inactive commuting tended to be associated with larger gain in abdominal adiposity indicators. Conclusion Switching from inactive commuting mode to more physically active commuting mode and maintaining active commuting can promote body weight control among working adults across different levels of occupational or leisure-time physical activity.